Effect of COVID-19 vaccination on the outcome of in vitro fertilization: A systematic review and meta-analysis - Zhang, Linyu; Sun, Xinrui; Wang, Ruohan; Ma, Fang (Frontiers in Public Health, 2023)
Background Universal COVID-19 vaccination programs are now recommended in several countries and represent the most effective preventive measure against COVID-19. However, some reports suggest that vaccination may cause infertility or have adverse effects on pregnancy. Conflicting reports have led to vaccine hesitancy in women planning pregnancy. Purpose To determine whether vaccination against COVID-19 affects in vitro fertilization (IVF) outcomes, we conducted a meta-analysis. Method A systematic search was conducted using PubMed, Embase, MEDLINE, and Web of Science databases for all published literature on COVID-19 vaccines and outcomes of IVF. International Prospective Register of Systematic Reviews registration was completed on September 13, 2022 (CRD42022359771). Results We analyzed 20 studies totaling 18,877 individual cases undergoing IVF. COVID-19 vaccination had significant effect on clinical and ongoing pregnancy rate (risk ratio (RR): 0.97; 95% confidence interval (CI): 0.94–0.99; RR: 0.93; 95% CI: 0.87–0.99). These outcomes did not differ between vaccinated and unvaccinated individuals: biochemical pregnancy rate (RR: 0.95; 95% CI: 0.88–1.03), implantation rate (RR: 1.02; 95%CI: 0.97–1.07; P = 0.41), the number of oocytes (mean difference (MD): 0.12; 95% CI: −0.65–0.88) and MII/mature oocytes recovered (MD: 0.27; 95% CI: −0.36–0.90), blastocysts rate (MD: 0.01; 95% CI: −0.04, 0.06), and fertilization rate (MD: 1.08; 95% CI: −0.57, 2.73). Conclusion Our findings suggest that vaccination against COVID-19 does not adversely affect the biochemical pregnancy rates; number of oocytes and MII/mature oocytes obtained; implantation, blastocysts; and fertilization rates in women undergoing IVF treatment. Subgroup analysis showed that the mRNA vaccine had no statistical significance on all indexes (clinical, biochemical, or ongoing pregnancy rates; implantation, blastocysts, or fertilization rates; and the number of oocytes and MII/mature oocytes). The findings of this meta-analysis are anticipated to increase the willingness of women planning IVF treatment to receive COVID-19 vaccination and provide evidence-based medical guidance for the development and implementation of guidelines. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/, identifier: CRD42022359771.